PORNOGRAFI DALAM PERIKLANAN - Abidin, Kurniati (An - Nisa`, 2010)
This article see the pornography in advertisement, where placing women body as object. Pornography problem have been arranged in law and regulation like KUHP, UU number 40 year 1999 about pers, UU number 23 year 2002 about children protection, and UU number 44 year 2018 about pornography, but seems hitherto this problem is still pro and contra event that deduction come from the women itself.